Aplikasi Bacillus Sp. Melalui Pupuk Kandang Sapi Untuk Menekan Persentase Serangan Hama Wereng Coklat ( Nilaparvata lugens ) Pada Tanaman padi( Oryza Sativa L. ) - Gurusinga, Wandana (Cattleya Darmaya Fortuna, 2024)
The abstract should be clear and informative in one paragraph (between 150 and 300 words). Use the Book Antiqua font size 9 pt with single spacing. It should describe your entire paper in a concise manner containing an introduction indicating research gaps, objectives, methodology, findings, conclusions, and implications/contributions of the research. It should tell potential readers what you did and highlight key findings. Avoid using technical jargon and unfamiliar abbreviations. The abstract should appear at the top of the first page after the title, author. Email address of the corresponding author (who will handle correspondence at all stages of assessment and publication, as well as post-publication; this responsibility includes answering any future questions about the Methodology and Materials) of the paper. Keywords are your manuscript labels and are important for proper indexing and searching. They should be well chosen and closely related to the topic to make it easier for readers to find and should represent the content of your article. Use only abbreviations that are commonly used in the field. There should be 3-7 keywords (phrases). Each phrase in Keywords must be separated by a semicolon.